ANALYSIS OF LAND OWNERSHIP RESTRICTIONS FOR FOREIGNERS ACCORDING TO INDONESIAN LAW AND THAILAND LAW - Athaya, Syarifah Khaira; Astuti, Mirsa (Pena Cendekia Insani, 2026)
Land is a strategic resource closely linked to state sovereignty, public welfare, and economic stability. In the context of globalization and increasing foreign investment, Southeast Asian countries face the challenge of opening their property markets without undermining national interests. This study aims to analyze restrictions on foreign land ownership under Indonesian and Thai law and to compare the legal approaches of both countries. This research applies a normative legal method using statutory and comparative approaches. The findings indicate that Indonesia allows limited foreign access through use rights and condominium ownership, whereas Thailand maintains a stricter prohibition on direct land ownership by foreigners, allowing only narrow exceptions. Both countries seek to protect national land sovereignty but differ in their level of openness to foreign property investment.